Analisis Penerapan Kurikulum Merdeka pada Mata Pelajaran Pendidikan Agama Islam Kelas X di SMA Negeri 1 Ulakan Tapakis Kabupaten Padang Pariaman - Alfurqan; Khairara (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2023)
The research aims to describe the implementation of the Merdeka curriculum in the subject of Islamic Religious Education at SMA Negeri 1 Ulakan Tapakis. The study adopts a qualitative descriptive method with a phenomenological approach. The findings indicate that Islamic Religious Education teachers apply Problem-Based Learning strategies and utilize Audio-Visual learning media. In terms of assessment, teachers provide assignments, quizzes, and remedial sessions. The challenges in implementing the Merdeka curriculum include difficulties faced by teachers in creating lesson plans to determine the appropriate learning media, lack of updates on the use of strategies and learning media, and limited access to the internet. Teachers employ various efforts in implementing the Merdeka curriculum, such as evaluating attendance, competence, and activeness. They also receive training on the implementation of the Merdeka curriculum. The impact of implementing the Merdeka curriculum in Islamic Religious Education at SMA Negeri 1 Ulakan Tapakis is that students find it easier to comprehend PAI subjects, and they become more actively engaged in learning.